Annealing and sintering effects in thermoelectric skutterudites synthesized by gas atomization. Issue 3 (26th October 2015) - Schmitz, Andreas; Schmid, Carolin; Stiewe, Christian; de Boor, Johannes; Müller, Eckhard
Abstract : Skutterudites on the basis of CoSb3 are among the best thermoelectric materials for generator applications in the intermediate temperature range. Still, to be suitable for a wide range of applications methods for low cost fabrication of large amounts of this material are needed. A process potentially fulfilling these requirements is gas atomization plus consecutive short‐term sintering. As the powder produced by atomization is usually not single phase skutterudite material, the subsequent processes of sintering and eventually annealing prior to sintering play an important role for the resulting material's thermoelectric properties. In this work, we investigate the influence of powder annealing and sintering on the properties of indium‐filled skutterudites synthesized by gas atomization. The phase composition and thermoelectric properties are investigated as functions of the sintering temperature. Furthermore, the influence of an intermediate annealing step prior to sintering is investigated. It is shown short sintering times at temperatures around 450 °C are sufficient to achieve dense single phase skutterudite material from atomized powder whereas for annealed skutterudite powder sintering temperatures higher than 550 °C are needed for dense samples. Furthermore, sintering temperature and annealing are shown to have strong influences on the microstructure and thermoelectric properties of the material.